PENGARUH REBRANDING TERHADAP BRAND IMAGE “INDIHOME BY TELKOMSEL” PADA PELANGGAN - Rahiem, Vikry Abdullah; Hermawan, Vera (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT This study aims to analyze the impact of rebranding on the brand image of "IndiHome by Telkomsel." In an era of increasingly fierce business competition, companies are required to continuously adapt and update their image to remain relevant in the eyes of customers. The approach used in this study is quantitative with an explanatory survey method. Several theories underpinning this research include cognitive psychology theory, stimulus-organism-response theory, and organizational image management theory developed by Massey (2003). Through systematic random sampling techniques, a sample of 98 was obtained, comprising IndiHome by Telkomsel customers who are also followers of the Instagram account @indihomecare. Data in this study were collected through questionnaires, interviews, literature studies, and internet media. This study emphasizes the importance of strategic communication with stakeholders to build the desired image. The research methods used include the collection of primary and secondary data, as well as observational analysis of customer interactions on social media. The results of the study show that the rebranding carried out by IndiHome, including changes in name, logo, and slogan, has a significant impact on customer perception. This study also provides recommendations for further research to explore other aspects such as corporate social responsibility and advertising strategies used. Thus, this study is expected to provide deeper insights into the dynamics of rebranding in the context of internet services in Indonesia.